PROFICIENT IN ENGLISH WITH ADVANCED VOCABULARY USING GAME-BASED LEARNING: NARRATIVE CROSSWORD PUZZLE - Wahyuningsih, Yulia; Maretha, Carla (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research investigates the effectiveness of using Narrative Crossword Puzzles for learning advanced English vocabulary in the Society 5.0 era and how this method can enhance students' mastery of advanced vocabulary. This study demonstrates that the Game-Based Learning: Narrative Crossword Puzzle strategy significantly improves advanced English vocabulary learning. This research applied qualitative methods and an experimental quasi-technique with a statistical approach to analyze the data. The rejection of the null hypothesis confirms a substantial difference between pre-test and post-test results, indicating that the student's learning outcomes increased notably after implementing this strategy. The findings support the effectiveness of game-based learning, particularly narrative crossword puzzles, in enhancing student engagement and making the learning process more enjoyable and effective in educational contexts.